Analysis of The Potential Integrated Agricultural Sector in North Maluku Province - Nahu Daud; Irfan Zamzam; Muammil Sun’an; Sariffudin Fatmona; Hamidin Rasulu (International Journal on Food, Agriculture and Natural Resources, 2023)
Agriculture has an important role in human life because it serves as a provider of food, feed for livestock, and bioenergy. Realizing an integrated agricultural system in North Maluku Province is not an easy thing for the government, the community, or the business world. The purpose of this research is to analyze the potential of the integrated agricultural sector owned by each region and analyze the determination of location/region and integrated agricultural potential sector related to economic area development policy in North Maluku Province. As a result based on LQ value, almost all districts/cities in North Maluku Province on average have regional superior commodities according to sub-sectors (food crops, horticulture, plantations, and livestock), except Sula Islands Regency and Ternate City. Especially Sula Islands Regency, the superior commodities are plantation crops and livestock. In conclusion, by using an integrated agricultural approach has not fully applied the concept of integrated agriculture, both programmed under government agencies, companies, or self-help or community individuals. So it needs to be developed well integrated agricultural approach through the pattern of regional and sector/subsector approach into one unit by paying attention to environmental conditions for the realization of an integrated agricultural system in every regency/city in North Maluku Province.